An Improved Approach for Estimating Pan Evaporation Using a New Aerodynamic Mechanism Model. Issue 5 (12th May 2022) - Qiu, Guo Yu; Gao, Huihui; Yan, Chunhua; Wang, Bei; Luo, Jiechunyi; Chen, Zhi
Abstract: In response to a decline in pan evaporation over the last 60 years under global warming of water bodies, we designed an experiment with water bodies heated naturally to different temperatures to investigate the physics of pan evaporation and explore the effect of water temperature. In this study, we developed a new aerodynamic model for pan evaporation by combining a free convention sub‐model that couples Fick's First Law of Diffusion with boundary layer theory and a forced convection sub‐model based on convection mass transfer. Both the improved aerodynamic model and the two sub‐models have a higher accuracy and stability (|PBIAS| < 6%, root mean squared Error [RMSE] < 0.65 mm d −1, and Nash‐Sutcliffe efficiency [NSE] > 0.8). Sensitivity analysis shows that water temperature is the most sensitive parameter to evaporation ( S 1  = 0.58, S T  = 0.78). The mechanism of rising water temperature on evaporation is not only due to the strengthening in mass diffusion (under windless conditions), but also in the promotion in mass convection (under windy conditions). The integrated effects of mass diffusion and mass convection could result in an increase in evaporation of 0.8 mm d −1, as mean water temperature rises by 1°C. These results would be useful for evaporation estimation of the warming global water. Plain Language Summary: A new aerodynamic mechanism model is developed and verified by an innovative experiment. Both the improved aerodynamic model and its two sub‐models have a high accuracy and stability under different turbulence conditions. This new approach is also able to reveal the mechanism of rising water temperature on pan evaporation. This mechanism model illustrates an increase in water evaporation rate by 0.8 mm d −1 as water temperature rises by 1°C. Key Points: The improved aerodynamic model and its two sub‐models have a high accuracy and stability under different turbulence conditions An experiment with water bodies heated naturally is designed for model validation and to explore the effect of water temperature Water evaporation rate could increase by 0.8 mm d −1 as mean water temperature rises by 1°C